The Effect of Caring Training on Nurse’s Caring Behavior in Medical-Surgical Unit at Private Hospital in Medan - Tumanggor, Rustianna; Tambunan, Dior Manta; Sutriska Sagala, Martha (LLDIKTI Wilayah 1, 2024)
Caring is the essence of nursing as a fundamental of nurse’s career and the heart of nursing practice that it must be implemented by every nurse as a culture. The study objective is to identify the effect of caring training on nurse’s caring behavior in Medical-Surgical Unit at Private Hospital in Medan. The research method is Pre-Experimental design in one group pretest-posttest without control and 38 patients as respondents with random sampling technique. The result showed that pretest scoring before caring training on 20 patients (52.6%) as bad category and followed by 47.4% (18 patients) as quite good category. While the posttest scoring after caring training was increased significantly on 27 patients (71.1%) as good score and 11 patients (28.9%) as quite good score and a meaningful effect with p-value 0.000 (? <0.05). The study can be concluded, that there was a significant effect of caring training on nurse's caring behavior. The better nurse’s caring behavior in providing nursing care, the higher the level of patient satisfaction. It is expected that further researchers will add other variables such as motivation, workload, level of satisfaction, nurse work stress and implement emotional intelligence interventions or look for factors related to nurse’s caring